LEARNER WORKSHEETS AS A LEARNING EVALUATION FOR STUDENTS: AN ANALYSIS OF A STUDY OF SLOW LEARNER STUDENTS IN PRIMARY SCHOOL: LEMBAR KERJA PESERTA DIDIK SEBAGAI EVALUASI PEMBELAJARAN BAGI SISWA: ANALISIS STUDI SISWA SLOW LEARNER DI SEKOLAH DASAR - Sa’diyah, Halimatus; Arifin, Moch. Bahak Udin By (Educate : Jurnal Teknologi Pendidikan, 2025)
Education in Indonesia has the problem of inequality in accessibility as a citizens' constitutional right. Among these inequalities are inadequate infrastructure, poor quality of human resources, lack of learning resources, and many students who are classified as physically and mentally disabled have not received equal opportunities. Therefore, the study focuses on using Student Worksheets (LKPD) as a learning evaluation for slow learner students at SD Muhammadiyah 1 Sidoarjo. Using a qualitative case study approach, this study observes how LKPD is applied to support the learning process of students with slow learner. Observation, interviews, and documentation are used as data collection methods. The study results indicate that several stages are used to determine children who are shown as slow learners, namely by analyzing academic development, problem-solving, and difficulties in social interaction. The use of LKPD is effective in helping slow learner students understand the material by adjusting the level of questions according to their abilities and support from shadow teachers. LKPD can increase student involvement and facilitate more effective learning evaluation. In addition, remedial and diagnostic assessments help students achieve optimal understanding.